Examining Gifted Students' Evaluations of Their Education Programs in Terms of Their Project Production and Management - Özbek, Gülnur; Dağyar, Miray (Frontiers in Psychology, 2022)
The aim of this study is to examine gifted students’ evaluations of their education programs in terms of their project production and management by considering the basic principles of gifted education and training programs. In evaluating the effectiveness of programs for gifted students, it is regarded as important to consider the evaluations of the individuals for whom the programs are implemented. Project production and management was taken as the basis for the principles and guidelines of the programs implemented for gifted students. A mixed research design was used in the study. In the quantitative part of the research, the views of 300 randomly selected gifted students, who were attending the project production and management (PPM) and special talent development (STD) programs at Science and Art Centers (SACs) throughout Turkey, regarding their evaluation of the education programs, were analyzed. In the qualitative part of the research, the project production and management of the gifted individuals in the upper and lower groups according to their program evaluations were evaluated descriptively by examining the project proposals they developed. In the analysis of the quantitative data, it was determined that the participants had positive views about the effectiveness of the program, but that there was a significant difference between the upper and lower groups in terms of program evaluation scores. Considering this situation, the data of 10 participants in total (five participants included in each of the upper and lower groups) were subjected to qualitative analysis in the second stage. As a result of the study, it was determined that all of the gifted students in the upper and lower groups were able to produce projects, but that in the categories specified in their projects, there were differences in favor of the upper group in terms of depth, originality, taking their talents into account, acting consciously, acting in accordance with the plan, participating in more prestigious competitions, and quality.